Penentuan Kelayakan Pemberian Pinjaman Pada Koperasi Syariah Menggunakan Metode Simple Additive Weighting - Dalis, Sopiyan; Bahri, Syamsul; Cahyani, Gita (PROFITABILITAS, 2021)
Benteng Micro indonesia Cooperative (BMI) is one of the cooperatives engaged in the field of savings and loans. The assessment process for granting loans to cooperatives is still done manually so it requires quite a long time. In addition, the lending process is still subjective because without calculating the feasibility of lending it causes the risk of bad credit. Therefore, a decision support system is needed to determine who is more suitable to receive loans. The Simple Additive Weighting method is the best solution to solve the problems that exist in this cooperative, because with this method the decisions taken by cooperative members are more thorough and detailed than in the past. There are 5 criteria in determining the eligibility of loans, namely job criteria, income criteria, criteria for the form of collateral, criteria for the amount of the loan, criteria for funding requirements. The final results in this study in the form of ranking so that the cooperative can easily make decisions by looking at these results.